Implementation of Intercropping on Independent Palm Oil Plantation Based on Financial Feasibility Study - Oktoriana, Shenny; Hazriani, Rini; Romiyanto, Romiyanto (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2024)
The smallholder palm oil plantations in the Mayasopa Subdistrict, Singkawang City, West Kalimantan, have an average productivity of around 1.25 tons per hectare per year. Despite this, the palm oil plantation areas in this subdistrict have seen significant growth, reaching 668 hectares, which accounts for approximately 50% of all palm oil plantations in East Singkawang District. Given this trend, it is imperative to enhance the economic well-being of palm oil farmers by introducing alternative technologies that would not only increase food security and farmer income but also contribute to environmental preservation through the adoption of intercropping patterns. This study is focused on analyzing the financial viability of various intercropping plants. The research methodology involved a descriptive survey among 34 farmers who have implemented different intercropping plants. The financial feasibility of each intercropping plant variant was evaluated using the B/C ratio and farming income as critical measures. The findings indicate that in sequence, chilies, taro, and corn meet the criteria for financial viability in intercropping implementation. Based on these results, it is recommended that palm oil farmers consider introducing intercropping on their plantations, with a particular emphasis on cultivating chilies, which has been identified as the most financially viable option, to enhance their economic prospects.